2010
DOI: 10.1242/jeb.037069
|View full text |Cite
|
Sign up to set email alerts
|

Limits to sustained energy intake XII: is the poor relation between resting metabolic rate and reproductive performance because resting metabolism is not a repeatable trait?

Abstract: SUMMARYMany studies have investigated the consequences of individual variation in resting metabolic rate at thermoneutrality (RMRt) on reproductive performance. Despite strong theoretical reasons for expecting such an association, results have generally been disappointing. A fundamental assumption of these studies is that RMRt is a repeatable trait. We examined repeatability of RMRt in female MF1 mice over short (15days apart; N238) and long intervals (110days apart; N33). In the long-term experiment, afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 87 publications
4
35
1
Order By: Relevance
“…Higher milk output ability appears to result from the greater capacity for food intake and nutrient absorption of the mice with genetically determined high levels of BMR. It is also important, as we demonstrated in the multiparous animals, that the divergence between lines in viscera mass is retained after reproduction, whereas in non-manipulated populations, BMR (RMR) repeatability is lost after a reproductive bout (Duarte et al, 2010). Together, these findings provide support for the mechanism behind the assimilation capacity hypothesis for endothermy evolution in mammals (Koteja, 2000;Koteja, 2004) and highlight the significance and potential of long-term selection experiments in testing evolutionary scenarios.…”
Section: Research Articlesupporting
confidence: 64%
See 1 more Smart Citation
“…Higher milk output ability appears to result from the greater capacity for food intake and nutrient absorption of the mice with genetically determined high levels of BMR. It is also important, as we demonstrated in the multiparous animals, that the divergence between lines in viscera mass is retained after reproduction, whereas in non-manipulated populations, BMR (RMR) repeatability is lost after a reproductive bout (Duarte et al, 2010). Together, these findings provide support for the mechanism behind the assimilation capacity hypothesis for endothermy evolution in mammals (Koteja, 2000;Koteja, 2004) and highlight the significance and potential of long-term selection experiments in testing evolutionary scenarios.…”
Section: Research Articlesupporting
confidence: 64%
“…All of these processes, from food processing to milk synthesis, manifest themselves as a systematic elevation of metabolic rates in reproducing animals severalfold above what is most often quantified as the basal (measured at rest, in a post-absorptive state and within the thermoneutral zone, in nonreproducing individuals) or resting (measured at rest) metabolic rate (BMR or RMR). This phenomenon of lactation-induced elevation of metabolic rate in various mammal species has been well documented (Duarte et al, 2010) and can be regarded as the manifestation of the metabolic costs of lactation.…”
Section: Introductionmentioning
confidence: 91%
“…The significant repeatability of DEE in eastern chipmunks raises the possibility that this trait is heritable and thus may respond to selection (see Bergeron et al, 2011a), or be genetically correlated with other traits such as animal personality (Careau et al, 2008;Careau and Garland, 2012). An increasingly large number of studies report that RMR is significantly repeatable (reviewed by Duarte et al, 2010;Larivée et al, 2010;Nespolo and Franco, 2007) and heritable (reviewed by Careau et al, 2011). Despite the fact that we made several repeated measures on a large number of chipmunks, RMR was not repeatable in our population (sensu Bozinovic, 2007;Russell and Chappell, 2007).…”
Section: Repeatability Of Dee and Rmrmentioning
confidence: 80%
“…Repeatability in highly flexible traits should be expected only when the causes behind flexibility are controlled for (Naya, 2010) and our power to detect repeatability may have been diminished as our successive samples spanned reproductive events, seasons and years. Duarte and colleagues found that RMR was repeatable in female non-reproductive mice over a relatively long interval (110days), but was not repeatable when a reproductive event separated the measurements (Duarte et al, 2010), and this may also be the case for chipmunks. Food availability in the burrow, the intensity of torpor expression and the heat increment of feeding are some of the un-quantified conditions that may have affected RMR measurements.…”
Section: Repeatability Of Dee and Rmrmentioning
confidence: 99%
“…We have previously studied the responses to reproduction in the outbred MF1 mouse, focusing in particular on sustained energy intake in lactation (Duarte et al, 2010;Johnson et al, 2001b;Johnson and Speakman, 2001;Król et al, 2007;Król and Speakman, 2003a;Speakman and Król, 2011). In the current paper, we used this same model system to explore the patterns of change in food intake, body mass, thermoregulation and physical activity throughout pregnancy to establish the extent to which energy budgets in pregnancy may be compensated by changes in body temperature and physical activity.…”
Section: Introductionmentioning
confidence: 99%